PENINGKATAN KEMAMPUAN MENYIMAK CERITA ANAK DENGAN METODE LATIHAN SISWA KELAS IV SDN 005 ROKAN IV KOTO - Padmalinda Padmalinda (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to improve the ability to listen to children's stories class IV SDN 005 Rokan IV Koto through student training methods. The instrument of this research consists of instrument of activity sheet of teacher and student and test result of learning. The results of this study found that the average student on the preliminary test was categorized average with an average value of 63.20 and in the first cycle rose to 67.20 with low category, whereas in cycle II the average ability of students was categorized high with average value average 82, and 96% complete, where the value of student completeness has been achieved. This shows that the students 'ability to listen to children's story with the fourth grade students' training method SDN 005 Rokan IV Koto can be improved through the practice method.